PARAMETERS FOR THE EVALUATION OF CERVICAL SAGITTAL BALANCE IN IDIOPATHIC SCOLIOSIS - LIMA,MAURICIO COELHO (2017)
ABSTRACT Objective: There are no values defined as standard in the literature for the parameters of assessment of cervical sagittal balance in patients with idiopathic scoliosis. This study describes the sagittal cervical parameters in patients with idiopathic scoliosis. Methods: Study carried out in a tertiary public hospital in patients with adolescent idiopathic scoliosis, through the evaluation of panoramic radiographs in lateral view. The Cobb method was used to evaluate cervical lordosis from C2 to C7, distance from the center of gravity (COG) of the skull to C7, measurement of T1 slope, thoracic inlet angle (TIA), neck tilt, and plumb line from C7 to S1 (SVA C7-S1). A statistical analysis was performed, to demonstrate the relationship between the alignment of the thoracic spine in the sagittal plane and the cervical sagittal balance of patients with scoliosis. Results: Thirty-four patients were female (69.4%) and 15 male (30.6%). The mean values for COG-C7 were 0.71 mm (median 0.8 mm/standard deviation [SD]= 0.51 mm). For Cobb C2-C7, the mean was -11.7° (median -10°/SD= 20.4°). The mean slope of T1 was 23.5° (median 25°/SD= 9.5°). The mean cervical version was 58.8° (median 60°/DP= 15.4°). The mean TIA was 81.8° (median 85°/SD= 16.7°). The mean plumb line C7-S1 was -0.28 (-0.3/SD= 1.0). Conclusion: The analysis of the results showed that the mean values for the cervical lordosis are lower than the values described as normal in the literature, suggesting a loss of sagittal cervical balance in these patients.